English for office & business conversation : a picture process vocabulary = Tiếng Anh văn phòng & giao tiếp thương mại - Dean, Susan. (Nxb Trẻ, 2003)
Daily routines; Communication in the office; Handling printed materials; Postal/express mailing; Using telephones and faxes; Using computers and other office machines; Money matters; Maintaining the office.